Innovative AI applications in digital marketing: enhancing efficiency and sustainability - Abu Bakar, Elistina; Saidin, Aznan Zuhid; Haque, Mohammad Nadimul (Asian Scholars Network, 2024)
This research is a preliminary investigation on the impact of AI tools like ChatGPT and Midjourney on digital marketing. By leveraging AI, marketers can streamline content creation processes, reducing time and effort. Additionally, AI promotes sustainability by reducing the need for electronic resources, thus lowering energy consumption used in digital marketing. The study employs a quantitative methodology by studying a number of live marketing campaigns. Measurements from various campaigns were analysed to evaluate the practical benefits and challenges of using AI tools in digital marketing. The integration of AI tools in digital marketing has significantly enhanced efficiency, reduced resource usage, and improved overall marketing performance. Additionally, AI tools contributed to more sustainable marketing practices by halving the number of electronic devices required, thereby lowering energy consumption. While the study highlights certain benefits of AI in digital marketing based on actual marketing campaigns, it primarily provides initial results that require further study. Future research is needed to further investigate these findings and explore long-term impacts on consumer behaviour and brand loyalty. Marketers can achieve greater efficiency and promote sustainability by adopting AI-driven strategies. AI tools help optimise resource allocation, and enhance sustainability efforts, providing a competitive edge and aligning with consumer demand and promoting sustainable practices. This research provides insights into the practical application of AI in digital marketing, demonstrating its potential to improve efficiency and promote sustainability based on actual professional experience. It addresses the need for a nuanced understanding of AI's role in marketing and its broader implications for the industry.